Whole-Genome Sequencing of Linezolid-Resistant and Linezolid-Intermediate-Susceptibility Enterococcus faecalis Clinical Isolates in a Mexican Tertiary Care University Hospital - Pedro Martínez-Ayala; Leonardo Perales-Guerrero; Adolfo Gómez-Quiroz; Brenda Berenice Avila-Cardenas; Karen Gómez-Portilla; Edson Alberto Rea-Márquez; Violeta Cassandra Vera-Cuevas; Crisoforo Alejandro Gómez-Quiroz; Jaime Briseno-Ramírez; Judith Carolina De Arcos-Jiménez (Microorganisms)
Linezolid-non-susceptible Enterococcus faecalis (LNSEf) has emerged as a critical clinical concern worldwide, yet data from Latin American settings remain scarce. This study aimed to investigate the molecular epidemiology and mechanisms underlying LNSEf in a Mexican tertiary care university hospital, focusing on clinical correlates and clonal relationships. A total of 392 non-duplicated E. faecalis isolates were collected over 12 months, of which 24 with minimum inhibitory concentrations ≥4 µg/mL underwent whole-genome sequencing to identify specific resistance determinants (optrA, cfrA, 23S rRNA mutations) and to perform multilocus sequence typing (MLST) and phylogenetic analyses. Of the 392 isolates, 6.12% showed linezolid non-susceptibility, predominantly linked to plasmid- or chromosomally encoded optrA; only two isolates carried cfrA. No mutations were detected in 23S rRNA domain V or ribosomal proteins L3/L4. Clinically, LNSEf strains were associated with immunosuppression, previous surgical interventions, and prolonged hospital stays. Although most LNSEf isolates retained susceptibility to ampicillin, vancomycin, and daptomycin, they exhibited high rates of resistance to other antibiotic classes, particularly aminoglycosides and fluoroquinolones. These findings underscore the emergence of LNSEf in this region, highlighting the need for robust genomic surveillance, strict infection control, and judicious antimicrobial stewardship to curb further dissemination.